2011
DOI: 10.3109/15622975.2011.562242
|View full text |Cite
|
Sign up to set email alerts
|

Stroke lesion in cortical neural circuits and post-stroke incidence of major depressive episode: A 4-month prospective study

Abstract: ObjectiveLittle is known about the relevance of lesion in neural circuits reported to be associated with major depressive disorder. We investigated the association between lesion stroke size in the limbic-cortical-striatal-pallidal-thalamic (LCSPT) circuit and incidence of major depressive episode (MDE).MethodsWe enrolled 68 patients with first-ever ischemic stroke and no history of major depressive disorder. Neurological and psychiatric examinations were performed at three time-points. We diagnosed major depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1
23

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 55 publications
3
73
1
23
Order By: Relevance
“…This variability may be related to the variety of instruments utilized to assess depressive symptoms as well as the inclusion of patients with language difficulties, which limits the comprehension of depression scales and inventories (in rehabilitation, ambulatories or hospitals). Although some studies suggested increased frequency of depression related to the left-hemisphere, mainly associated with left anterior lesions, little focus has been given to the cognitive consequences of SSD in patients with right-hemisphere lesion (5,8) . Thus, there is still a prominent lack of epidemiologic data on depression unilateral following post-stroke.Considering the aim to verify whether there is an influence of post-RHD depression in eight cognitive functions, in a general perspective RHD+ adults presented cognitive changes in at least one subtest in all neuropsychological domains assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability may be related to the variety of instruments utilized to assess depressive symptoms as well as the inclusion of patients with language difficulties, which limits the comprehension of depression scales and inventories (in rehabilitation, ambulatories or hospitals). Although some studies suggested increased frequency of depression related to the left-hemisphere, mainly associated with left anterior lesions, little focus has been given to the cognitive consequences of SSD in patients with right-hemisphere lesion (5,8) . Thus, there is still a prominent lack of epidemiologic data on depression unilateral following post-stroke.Considering the aim to verify whether there is an influence of post-RHD depression in eight cognitive functions, in a general perspective RHD+ adults presented cognitive changes in at least one subtest in all neuropsychological domains assessed.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, when comparing what has been found about cognitive impairment following a stroke in isolation (7) , as well as cognitive changes following depression cases (8) , little is known about the relationship between depression, unilateral right-hemisphere stroke and cognitive deficits derived by the association of these aspects. Thus, there is an important lack of knowledge on the comprehension of cognitive impairment associated with stroke and depression versus hemispheric specializations.…”
Section: Introductionmentioning
confidence: 99%
“…Uma importante metanálise que examinou 17 estudos prospectivos e um total de 206.641 indivíduos identificou que sintomas depressivos aumentam significativamente o risco de AVC e que esses achados podem ser independentes de outros fatores de risco como HAS e DM 34 . Terroni et al 35 ressaltam a complexa relação entre AVC e depressão e vice--versa. Os autores descrevem que os sintomas depressivos e a própria depressão já podem ser diagnosticados na segunda semana pós-evento em 27% dos casos, e a prevalência aumenta de acordo com a gravidade das limitações que são impostas 35 .…”
Section: Doenças Crônicas: Depressão Em Idososunclassified
“…Terroni et al 35 ressaltam a complexa relação entre AVC e depressão e vice--versa. Os autores descrevem que os sintomas depressivos e a própria depressão já podem ser diagnosticados na segunda semana pós-evento em 27% dos casos, e a prevalência aumenta de acordo com a gravidade das limitações que são impostas 35 . Diante disso, torna-se importante ressaltar que o AVC, assim como a maioria das DCNT, tem etiologia multifatorial e com diferentes prognósticos associados.…”
Section: Doenças Crônicas: Depressão Em Idososunclassified
“…However, in the past few years the hypothesis of PSD and PSA being associated with damage to specific lesion locations has been shifted to the idea that damage to a neuronal network involved in affect is underlying the development of PSD and PSA, [146][147][148] with different sub-circuits involved in PSD 90 and PSA, 145 see Table 4. DTI is a promising tool to identify more accurately how these brain networks are affected after stroke.…”
Section: Discussionmentioning
confidence: 99%